PHOX2B Mutation in a Taiwanese Newborn with Congenital Central Hypoventilation Syndrome - Tzu-Chiang Wang; Yi-Ning Su; Ming-Chi Lai (Pediatrics and Neonatology)
Congenital central hypoventilation syndrome (CCHS) is characterized by defective automatic regulation of breathing, mostly during sleep. The diagnostic criteria of CCHS include persistent sleep hypoventilation without primary cardiac, pulmonary disease or neuromuscular dysfunction, and no arousal response to hypoxemia and hypercapnia. Mutations in the PHOX2B gene have been indentified in 93–100% of patients with CCHS. We report a CCHS case with presentation of hypoventilation during sleep and Hirschsprung disease; moreover, a genetic study of the patient confirmed the PHOX2B gene mutation as polyanaline stretch.